2017
DOI: 10.1103/physreva.96.053608
|View full text |Cite
|
Sign up to set email alerts
|

Superfluid density and critical velocity near the Berezinskii-Kosterlitz-Thouless transition in a two-dimensional strongly interacting Fermi gas

Abstract: We theoretically investigate superfluidity in a strongly interacting Fermi gas confined to two dimensions at finite temperature. Using a Gaussian pair fluctuation theory in the superfluid phase, we calculate the superfluid density and determine the critical temperature and chemical potential at the Berezinskii-Kosterlitz-Thouless transition. We propose that the transition can be unambiguously demonstrated in cold-atom experiments by stirring the superfluid Fermi gas using a red detuned laser beam, to identify … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…More important role of the fluctuations in lower dimensions is in agreement with the Ginzburg-Levanyuk criterion [22,23]. Note also that in recent years a considerable numerical effort has been applied to the problem of the BCS-BEC crossover in 2D in the framework of the advanced mean field [21,24], Monte-Carlo simulations [25,26,27,28], and Luttinger-Ward (thermodynamic) identities [29]. Also a generalization of Nozières-Schmitt-Rink approach [9] with gaussian fluctuations to the 2D case was performed [20,30].…”
Section: Two-body and Many-body Physics In 2dmentioning
confidence: 67%
See 1 more Smart Citation
“…More important role of the fluctuations in lower dimensions is in agreement with the Ginzburg-Levanyuk criterion [22,23]. Note also that in recent years a considerable numerical effort has been applied to the problem of the BCS-BEC crossover in 2D in the framework of the advanced mean field [21,24], Monte-Carlo simulations [25,26,27,28], and Luttinger-Ward (thermodynamic) identities [29]. Also a generalization of Nozières-Schmitt-Rink approach [9] with gaussian fluctuations to the 2D case was performed [20,30].…”
Section: Two-body and Many-body Physics In 2dmentioning
confidence: 67%
“…One may see that the Gaussian is off both at the edges and center. For interacting Fermi and Bose gases, the numerical density profiles differ from profile (24). Despite that, since at T = 0 the dependence of the chemical potential on the density is nearly linear (μ ∝ n) [76], the closeness of the density profile to (23) firmly indicates a deep degeneracy and a smallness of the temperature with respect to E F and chemical potentialμ = µ + |E b |/2.…”
Section: Degeneracy Detection and Thermometrymentioning
confidence: 87%
“…To consider the BKT transition the superfluid density needs to be calculated for the two-channel model in the superfluid phase, following the work in Ref. [33]. Such a scheme is beyond the scope of this work.…”
Section: The Many-body T -Matrixmentioning
confidence: 99%
“…Very recently, the BCS-BEC crossover has also been realized in quasi two-dimensional (2D) configurations [7][8][9][10]. Beyond-mean-field theoretical investigations of 2D Fermi gases in the full BCS-BEC crossover have been carried out both at zero and finite temperature [11][12][13][14][15][16][17]. These 2D results have clearly shown that contrary to the 3D case, mean-field theories are completely unreliable for the study of strongly-interacting superfluid fermions in two dimensions because of the huge increase of quantum fluctuations.…”
Section: Introductionmentioning
confidence: 99%